Peran Ojk Dalam Perlindungan Nasabah Bmt Ilegal: Studi Kasus BMT Global Insani - Novitasari, Tita (Hukum dan Masyarakat Madani, 2019)
Baitul maal wa tamwil (BMT) is a sharia microfinance institution that can operate with cooperative legal entities, limited liability companies, even foundations or not incorporated. But the rules regarding the establishment of this BMT then changed after the enactment of Law No. 1 of 2013 about Microfinance Institutions (UULKM). At first the BMT was under the supervision of the Ministry of Cooperatives and Medium/ Small Business (for BMT with cooperative forms), and the Financial Services Authority (FSA/ Otoritas Jasa Keuangan/ OJK) was not authorized to BMT. But after the UULKM, the involvement of the OJK became dominant to the BMT. Now the establishment of BMT is mandatory under the OJK's permission, otherwise the BMT is illegal. This paper discusses how the legal basis/ status of BMT, as well as how the role of the OJK in protecting customers of illegal BMT (case study of Global Insani BMT). Even though illegal BMTs are not under the supervision of the OJK, they are still an obligation of the OJK when the BMT has proven to be detrimental to the customer, especially if it is against the law.
Keywords: Legal basis of BMT; illegal BMT; customer protection.